Ascend - Hocking, Amanda (St. Martin's Griffin, 2012)
Duty-bound to marry her friend Tove in order to give the Trylle people their strongest king and queen in history, Wendy, a changeling troll princess, is torn between two other suitors, Finn and Loki.